From Promotion to Strategic Branding: Educational Service Marketing Management in Building Madrasah Brand Image - Merrina Ulfa; Irawati Irawati; Rini Setyaningsih; Umar Faruq; Edi Iskandar (Managere: Indonesian Journal of Educational Management, 2026)
This study aims to examine how educational service marketing management builds the brand image of Madrasah. Increasing competition among educational institutions requires madrasahs to communicate institutional values, service quality, and religious identity more strategically. However, many schools still conduct promotion incidentally, without integrated branding and continuous evaluation. This study used a qualitative descriptive approach with purposive site and informant selection. Data were collected through interviews, observation, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings reveal that the madrasah applies structured marketing through planning, implementation, and supervision. Marketing activities involve principals, teachers, staff, and students through brochures, school visits, banners, community interaction, and social media. Nevertheless, digital media is still used mainly for documentation rather than strategic brand storytelling. The study also found that affordable tuition, competent teachers, strategic location, and a clean religious environment strengthen public trust and positive perception. Meanwhile, limited facilities, increasing competition, and weak digital branding constrain marketing effectiveness. This study contributes to educational marketing literature by showing that madrasah brand image emerges from integrated communication, service quality, and Islamic institutional culture.